Vitreous proteomics in rhegmatogenous retinal detachment and proliferative vitreoretinopathy - Havlik, Jan; Lada, Martin; Tesar, Jan; Kratky, Vladimir; Sin, Martin (Biomedical papers, 2025)
Rhegmatogenous retinal detachment (RRD) is a serious ophthalmic condition that, if untreated, can result in significant vision loss. Proliferative vitreoretinopathy (PVR) often complicates RRD and is the leading cause of surgical failure. Proteomic analysis of the vitreous has emerged as a powerful tool for elucidating the molecular mechanisms underlying RRD and PVR. This article reviews proteomic findings related to these conditions. A comprehensive literature search on PubMed was conducted, focusing on studies of vitreous proteomics in RRD and PVR published between 1988 and August 2024. Relevant findings on protein expression, metabolic pathways, and therapeutic targets were synthesized. Proteomic studies reveal significant alterations in photoreceptor-specific proteins, such as rhodopsin and Monocyte Chemoattractant Protein-1 (MCP-1), associated with apoptosis and inflammation during RRD. Metabolic dysregulation is evidenced by changes in glycolytic enzymes and antioxidants, including downregulation of peroxiredoxin-2 and ascorbic acid, suggesting impaired energy production and oxidative stress. Elevated cytokines, complement proteins, and matrix metalloproteinases highlight the role of inflammation and extracellular matrix remodelling in disease progression. Cytokine expression in PVR demonstrates distinct temporal patterns, with early stages marked by T-cell activation and mTOR pathway-related cytokines, and advanced stages characterized by monocyte chemoattractants associated with chronic inflammation. Currently, the potential of pharmacologic interventions in RRD and PVR remains limited. In contrast, proteomics offers critical insights into molecular mechanisms, identifying potential biomarkers and therapeutic pathways. The adoption of single-molecule and top-down proteomics, along with the integration of advanced technologies with artificial intelligence and bioinformatics, holds promise for accelerating progress toward precision medicine. These developments represent a promising avenue for future research and clinical application.
Keywords: proteomics; mass spectrometry; vitreous; rhegmatogenous retinal detachment; proliferative vitreoretinopathy